2016
DOI: 10.1002/prp2.231
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory, antiapoptotic, and antioxidant activity of fluoxetine

Abstract: Fluoxetine is a selective serotonin uptake inhibitor that has been widely used to determine the neurotransmission of serotonin in the central nervous system. This substance has emerged as the drug of choice for the treatment of depression due to is safer profile, fewer side effects, and greater tolerability. Studies have found the following important functions of fluoxetine related to the central nervous system: neuroprotection; anti‐inflammatory properties similar to standard drugs for the treatment of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 81 publications
(172 reference statements)
5
58
0
Order By: Relevance
“…It may be relevant in this respect that fluoxetine is known to act as a serotonin reuptake inhibitor (Caiaffo et al . ), and that the S100B and serotonin (5‐HT) systems are believed to be interconnected (Azmitia et al . ; Whitaker‐Azmitia et al .…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 99%
“…It may be relevant in this respect that fluoxetine is known to act as a serotonin reuptake inhibitor (Caiaffo et al . ), and that the S100B and serotonin (5‐HT) systems are believed to be interconnected (Azmitia et al . ; Whitaker‐Azmitia et al .…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 99%
“…Previous reports showed that Fluoxetine is a selective serotonin reuptake inhibitor (SSRI) that has been widely used to modulate the concentration of serotonin in the central nervous system . It is well‐known as Prozac for the treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that Fluoxetine is a selective serotonin reuptake inhibitor (SSRI) that has been widely used to modulate the concentration of serotonin in the central nervous system. 18 It is well-known as Prozac for the treatment of depression. Actually, there is encouraging evidence demonstrating that Fluoxetine interferes with mitochondrial function and may induce cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoxetine has been studied in different animal models of neurological disorders, including Parkinson’s disease, Down syndrome and ischemic brain injury (Zhu et al, 2012; Guidi et al, 2014; Caiaffo et al, 2016). Different molecular mechanisms have been proposed to explain its neuroprotective effects, including BDNF release (Chang et al, 2006), antagonism on NMDA receptors (Vizi et al, 2013), inhibition of NF-kappa B activity (Lim et al, 2009), and inhibition of the release of pro-inflammatory factors (TNF-α, IL-1β) from microglial cells (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%